2019
DOI: 10.1177/1179544119877170
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Results of the PHANTOM High Flex Trial: A Single-Arm Study on the Atlas Unicompartmental Knee System Load Absorber in Patients With Medial Compartment Osteoarthritis of the Knee

Abstract: The Atlas Knee System was designed to fill the gap between no longer effective conservative treatments and more invasive surgery for young patients with medial knee osteoarthritis (OA). This article reports on the 2-year results of a single-arm study of 26 subjects who previously reported favorable clinical outcomes 1 year post implantation. Western Ontario and McMaster Universities Osteoarthritis Index pain and function scores improved by a clinically meaningful amount relative to baseline, and subjects had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
2
14
0
2
Order By: Relevance
“…Patients without baseline SIFK were excluded. Patients from a previously published prospective study utilizing the ISA [11] were matched to controls using the SIFK Score as detailed below in an exact manner using a matching software which matches cases and controls in a random manner (MedCalc 19.2.6, MedCalc Software Ltd, Ostend, Belgium). Patient demographic and radiographic parameters were collected.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients without baseline SIFK were excluded. Patients from a previously published prospective study utilizing the ISA [11] were matched to controls using the SIFK Score as detailed below in an exact manner using a matching software which matches cases and controls in a random manner (MedCalc 19.2.6, MedCalc Software Ltd, Ostend, Belgium). Patient demographic and radiographic parameters were collected.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[G Bode reference, Oliver Morgan reference] Twoyear results of a prospective single-arm study revealed significant benefits with regards to WOMAC pain and function scores without significant adverse effects. [11] Still, there are no comparative studies on evaluating this implant system comparted to non-operative controls with regards to progression to arthroplasty. [11] Therefore, the purpose of the current study was to evaluate whether partially unloading the knee with ISA altered the likelihood that a patient with SIFK will progress to knee arthroplasty utilizing a validated predictive risk model based on demographic and radiographic characteristics (the SIFK score).…”
Section: Introductionmentioning
confidence: 99%
“…W badaniu Slynarski i in. [16,18] dokonano oceny 26 pacjentów początkowo po 12 miesiącach leczenie następnie po 24 miesiącach leczenia. Po 12 miesiącach leczenia zaobserwowano znaczną poprawę w skali KSS z 61.9 ± 3.0 do 94.6 ± 1.6.…”
Section: Iva Atlas Knee System -Konstrukcja I Mechanizm Działaniaunclassified
“…U jednej wykonano artroskopię kolana z mikrozłamaniami. U jednego pacjenta wykonano artroskopię, usunięto łąkotkę oraz osteofity [18]. Do tej pory nie opisano w literaturze żadnej infekcji i rewizji implantu.…”
Section: Ivc Atlas Knee System -Ograniczeniaunclassified
“…71 Production of catabolic cytokines such as interleukin (IL)-1 and tumor necrosis factor (TNF)-a were decreased. Other joint-saving techniques with partial unloading such as tibial osteotomy or unicompartmental load absorbing implants (Atlas system) show clinical 72 and even structural beneficial changes. [73][74][75] Both techniques significantly reduce (medial) compartment contact pressure and peak contact pressure 76,77 and maintain joint fluid pressure oscillations as well.…”
mentioning
confidence: 99%